Penghilangan Senyawa Fenol Oleh Bakteri Yang Diisolasi dari Area Pertambangan Minyak Bumi - Joko Prayitno (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2016)
The aim of this research was to study the effectiveness of local bacterial strains from oil-contaminated soil to degrade phenol. The study consisted of two experiments, using six individual strains and using mix of strains. Bacterial strains used in the first experiment were 1.3, 3.3 dan 8.2.1 (Bacillus sp.), strain 3.2 (Propionibacterium), strain 3.4 (Pseudomonas sp.), and strain 8.1.2 (Enterobacter sp.).Bacterial strains used in the second experiment were mix of all six strains (K6) and mix of three strains (K3) consisted ofÂ strain 3.4, 8.1.2 and 8.2.1 with the same ratio. The experiments were conducted in 100 mL Bushnell and Haas medium containing 300-400 ppm phenol for three days.Three strains (strain 3.4, 8.1.2, dan 8.2.1) had the highest phenol removal efficiency at day 3, i.e. 99-100%. COD values were decreased to 345-393 mg/L or 56-61.3% by those three strains. Mix culture K6 effectively removed phenol form the medium, but COD value decreased to only 56.7%. The fate of COD decrease was not the same as phenol removal by these strains (either in idividual or mix cultures), because phenol was degraded into intermediate compounds.Â